2018
DOI: 10.1186/s13104-018-3538-8
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of hepatitis B virus infection and associated factors among health care workers and medical waste handlers in primary hospitals of North-west Ethiopia

Abstract: ObjectiveThe aim of this cross-sectional study was to determined the sero-prevalence of HBV infection and associated factors among health care workers and medical waste handlers in primary hospitals of North-west Ethiopia.ResultsA total of 388 study participants were included in this study. Of which, 268 (69%) were health care workers and 120 (31%) were medical waste handlers. Males accounted 54.9% and the mean age for all study participants was 28.3 (standard deviation = 6.9). Hepatitis B virus surface antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
5
16
3
Order By: Relevance
“…HBV can remain on any surface it comes in contact with for about a week, particularly on table-tops, razor blades, and bloodstains, without losing its infectivity [ 21 ]. This result is similar to the previous studies conducted in northwest Ethiopia and Nigeria [ 1 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…HBV can remain on any surface it comes in contact with for about a week, particularly on table-tops, razor blades, and bloodstains, without losing its infectivity [ 21 ]. This result is similar to the previous studies conducted in northwest Ethiopia and Nigeria [ 1 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Hepatitis is a major public health conundrum that results in mortality and morbidity worldwide [ 1 ]. Hepatitis B virus is a hepatotropic DNA virus that causes the immune-mediated killing of infected liver cells [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The earliest study was conducted during 2009 [55], and the latest two articles were published in 2019 [58, 59]. Overall information regarding the prevalence of NSIs was obtained from five regions and two self-administrative cities including Amhara [41, 44, 47, 49, 51, 53, 5759]; Oromia [42, 48, 56]; Southern Nations, Nationalities, and People (SNNP) [37, 46, 50]; Somali [38]; and Harari [43]; two studies were conducted on both Somali and Dre Dawa (SAC) [52, 55], and four articles were obtained from two self-administrative cities Addis Ababa and Dire Dawa [39, 40, 45, 54]. The sample size across the studies was ranged from 162 [37] to 760 [46].…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies, ten articles exclusively reported the 12-month NSI prevalence [38, 41, 42, 44, 5053, 55, 56]. Similarly, seven studies exclusively reported the lifetime prevalence of the NSI [37, 39, 40, 47, 54, 57, 58]. The remaining five articles have reported both the 12-month and lifetime needlestick injury prevalence [43, 45, 46, 48, 49, 59].…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiologic evidence shows that a considerable percentage of people with severe psychiatric disorders had comorbid viral infections such as human immunodeficiency virus infection (HIV) 6.2-29.10% [7][8][9][10], hepatitis B virus (HBV) 7.45-47.5% [10][11][12][13], as well as hepatitis C virus (HCV) 6.2-29.8% [7,10,13,14] infections at some point in their lives. These prevalence estimates are considerably higher than the reported prevalence in the general population [15][16][17][18]. In Ethiopia, the estimated prevalence of HIV, HBV, and HCV were 0.66% [15], 6.3% [16], and 3% [16] respectively.…”
Section: Introductionmentioning
confidence: 88%